Caracterização ambiental e investigação da presença de metais traço na coluna d agua e no sedimento do Rio Piranhas, São Bento, Paraíba - Barros, Sara Regina Ribeiro Carneiro de (2010)
Due to the intense activity in the textile business Piranhas River, which traverses the city of São Bento-PB is serving as the depletion for the waste generated in the steps of bleaching and dyeing of yarn, since the networks are made by artisans, many them in the backyards of residences. On this context, for this work, we collected water and sediment samples at three different points of the Piranhas, with the objective to evaluate a possible contamination of these compartments resulting from dumping of textile effluent. Were also determined the variables Dissolved Oxygen (DO), Total Dissolved Solids (TDS), OM (Organic Matter), Conductivity, pH and temperature. The results obtained for these parameters are consistent with those expected for the location of the environment under study, where the rainfall is marked by extreme irregularity. An analysis screening using the voltammetry technique was used to indicate the presence of trace metals in water, this analysis showed the possible presence of metals, Zn, Pb and Cu. Concerning the sediment samples, the quantitative analysis performed using the technique of ICP-MS (Inductively Coupled Plasma-Mass Spectrometry) showed that among the investigated metals, Cd, Pb, Cu, Cr, Ni, Cr and Ni elements were those with higher levels during the study period. Using parameters of the sediment quality evaluators, it was observed that the metals Cr and Ni had values that exceeded the lower limit TEL (Canadian guideline value) thus indicating a deleterious made occasional on aquatic biota of the environment under study. Principal components analysis (PCA) using variables such as the physical-chemical parameters and concentrations of metals investigated, highlighted the influence of parameters and STD Conductivity, pH and organic matter in the grouping of data and also showed that the differences in metal contents between months in the study (rainy and dry) were more relevant than the differences between the sampling sites investigated. From the results and taking into account the variables measured along the river, it was found that there is no evidence that the textile wastewater at the moment, is affecting the characteristics of the Piranhas.